Strengthening the Regulation of Pokjanal and Pokja from District or City Posyandu in Aceh: A Strategic Study Based on Policy Brief - Irnawati, Irnawati; Seriana, Irma; Ibrahim, Ibrahim; Sumihardi; Hayati, Wirda (Journal Keperawatan, 2025)
Background:  The transformation of health services through the rebranding of Integrated Health Posts (Posyandu) as a community-friendly service positioned Posyandu as the primary hub for community-based health services, with a lifecycle approach, from pregnant women to the elderly. However, in Aceh Province, Posyandu's functioning still faces challenges such as limited funding, unequal capacity of cadres, and the suboptimal institutional role of the Posyandu Operational Working Group (Pokjanal) and Working Group (Pokja). Purpose: To compile policy recommendations in the form of a policy brief regarding the formation and strengthening of regulations for Pokjanal and Pokja Posyandu at the district/city level in Aceh. Methods: The research employed a strategic review approach based on a policy brief. Data were collected through focus group discussions (FGDs) and in-depth interviews with stakeholders, including the Ministry of Home Affairs, the Ministry of Health, the Health Office, the Community Empowerment Office, the Family Welfare Movement (PKK), the Integrated Health Service Post (Posyandu) working group (Pokjanal), and the National Population and Family Planning Board (BKKBN). Data were analyzed qualitatively through thematic synthesis to formulate policy recommendations. Results:  The findings show that 54% of Posyandu in Aceh are not yet active. Posyandu working groups at the district/city and sub-district levels are not yet functioning optimally, while Posyandu working groups at the village level are still limited. Synthesis of the results of FGDs and interviews resulted in nine policy recommendations, including: socialization of Posyandu's position as a Village Community Institution; affirmation of Posyandu's function as a forum for health and social activities; strengthening the role of working groups in services; increasing the capacity of cadres based on 25 basic competencies; structuring the management structure through Village Regulations/Village Decrees; strengthening lifecycle-based and cross-sectoral services; harmonizing regulations following Law No. 17/2023 concerning Health; and regulating cadre terms of office and incentives. Conclusion: Optimizing Posyandu in Aceh requires derivative regulations at the district/city level for the formation and strengthening of Pokjanal-Pokja, accompanied by clear institutional support and increasing the capacity of Posyandu cadres so that integrated health services can be sustainable.